2017
DOI: 10.5194/acp-17-12645-2017
|View full text |Cite
|
Sign up to set email alerts
|

Summertime OH reactivity from a receptor coastal site in the Mediterranean Basin

Abstract: Abstract. Total hydroxyl radical (OH) reactivity, the total loss frequency of the hydroxyl radical in ambient air, provides the total loading of OH reactants in air. We measured the total OH reactivity for the first time during summertime at a coastal receptor site located in the western Mediterranean Basin. Measurements were performed at a temporary field site located in the northern cape of Corsica (France), during summer 2013 for the project CARBOSOR (CARBOn within continental pollution plumes: SOurces and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…10 An exponential temperature dependence of the missing reactivity was observed during two campaigns carried out in the same North American forest, consistent with either primary biogenic emissions (Di Carlo et al, 2004) or with their oxidation products (Hansen et al, 2014). Some of the campaigns carried out in other forested environments also observed a similar trend (Kaiser et al, 2016;Mao et al, 2012;Zannoni et al, 2017), whereas others found no evidence for this correlation (Ren et al, 2006b;Sinha et al, 2010). 15 In an attempt to account for the additional OH reactivity potentially arising from unmeasured oxidation intermediates, a number of studies invoked box modelling to determine the abundance of these species and their contribution to kOH.…”
Section: Introductionmentioning
confidence: 63%
“…10 An exponential temperature dependence of the missing reactivity was observed during two campaigns carried out in the same North American forest, consistent with either primary biogenic emissions (Di Carlo et al, 2004) or with their oxidation products (Hansen et al, 2014). Some of the campaigns carried out in other forested environments also observed a similar trend (Kaiser et al, 2016;Mao et al, 2012;Zannoni et al, 2017), whereas others found no evidence for this correlation (Ren et al, 2006b;Sinha et al, 2010). 15 In an attempt to account for the additional OH reactivity potentially arising from unmeasured oxidation intermediates, a number of studies invoked box modelling to determine the abundance of these species and their contribution to kOH.…”
Section: Introductionmentioning
confidence: 63%
“…Some of the campaigns carried out in other forested environments also observed a similar trend (Kaiser et al, 2016;Mao et al, 2012;Zannoni et al, 2017), whereas others found no evidence for this correlation (Ren et al, 2006b;Sinha et al, 2010).…”
Section: Introductionmentioning
confidence: 86%
“…The advent of airborne measurements of OH reactivity (OHR) provides a method to evaluate the total sink of OH across a range of altitudes and a variety of locations and chemical environments (Mao et al, 2009). Previous work compared surface observations of OHR at a single site to the sum of individually calculated OHR components from measurements (Di Carlo, 2004;Yoshino et al, 2006;Sinha et al, 2008Sinha et al, , 2010Mao et al, 2010;Dolgorouky et al, 2012;Hansen et al, 2014;Nakashima et al, 2014;Nölscher et al, 2012Nölscher et al, , 2016Ramasamy et al, 2016;Zannoni et al, 2016Zannoni et al, , 2017 or from simple models (Ren et 10 al., 2006;Lee et al, 2009;Lou et al, 2010;Mogensen et al, 2011;Mao et al, 2012;Edwards et al, 2013;Kaiser et al, 2016;Whalley et al, 2016). Ferracci et al (2018) explored the impact of missing OHR estimated from surface observations on modeled global OH levels.…”
Section: Introductionmentioning
confidence: 99%